2021
DOI: 10.3390/ijms22169045
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling and Sarcopenia: Searching for the Primary Suspect

Abstract: Sarcopenia, the age-related decline in muscle mass and function, derives from multiple etiological mechanisms. Accumulative research suggests that reactive oxygen species (ROS) generation plays a critical role in the development of this pathophysiological disorder. In this communication, we review the various signaling pathways that control muscle metabolic and functional integrity such as protein turnover, cell death and regeneration, inflammation, organismic damage, and metabolic functions. Although no singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 196 publications
(300 reference statements)
1
29
0
Order By: Relevance
“…These results were consistent with the performance of mitochondrial dysfunction in diabetic skeletal muscle. A recent study had described that the glutathione pathway plays a positively substantial role in removing ROS and skeletal muscle mass by modulating redox homeostasis [42][43][44][45] which is consistent with our findings with the down-regulated glutathione pathway in db/db mice.…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with the performance of mitochondrial dysfunction in diabetic skeletal muscle. A recent study had described that the glutathione pathway plays a positively substantial role in removing ROS and skeletal muscle mass by modulating redox homeostasis [42][43][44][45] which is consistent with our findings with the down-regulated glutathione pathway in db/db mice.…”
Section: Discussionsupporting
confidence: 93%
“…TNFα, IL-1B, IL-1, and IL-6 also directly inhibit phosphoinositide 3-kinases (PI3Ks)/Protein kinase B (Akt) activity and protein synthesis pathway. In this way, IL-6 reduces skeletal muscle by signaling its receptor ( 14 ). In sarcopenia, there is an increase in the levels of inflammatory factors, including TNF-α, IL-1, and IL-6, and this increase is associated with a decrease in muscle mass.…”
Section: Interleukinsmentioning
confidence: 99%
“…Then activated NF-KB with FOXO1 acts synergistically, increasing the expression of pro-inflammatory factors such as IL-1β ( 114 ). On the other hand, inflammation is associated with FOXO activation and myostatin overexpression, which in turn can cause NF-KB-independent muscle atrophy ( 14 ). One study found that the expression of SMAD and FOXO increased myostatin promoter activity and inhibited myoblast differentiation ( 115 ).…”
Section: Effects Of Exercise and Sarcopenia Obesity On Protein Degrad...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, RNS can be neutralized by hemoglobin, uric acid, β-carotene, vitamins E and C, as well as by SOD, glutathione peroxidase and thioredoxin [ 127 ]. These antioxidant systems allow a fine-tune balance of ROS levels, and disruption of this equilibrium can cause OS, a condition implicated in the progression of different skeletal muscle affections, including sarcopenia and different types of myopathies [ 6 , 128 ]. The redox imbalance may be due to an increased production of O 2 •− or a reduced neutralization of ROS and RNS.…”
Section: Oxidative Stress In Muscular Dystrophiesmentioning
confidence: 99%